LAYANAN PURNA JUAL DALAM MEMBENTUK WOM (WORD OF MOUTH) PADA DAYA MOTOR CABANG PAYO SELINCAH KOTA JAMBI - Sylvia Kartika Wulan Bhayangkari; Fitri Widiastuti (Jurnal Manajemen Terapan dan Keuangan, 2020)
Abstract. This study was aimed to find out how the influence of After Sales Service in forming WOM (Word of Mouth). It was an explanatory research with quantitative approach. One hundred sample respondents were set by using conveinience sampling technique where the respondents were consumers of Daya Motor, Branch Payo Selincah in Kota Jambi. Data were analyzed descriptively and quantitatively. Quantitative analysis was performed by simple regression analysis. Results of descriptive analysis on consumers perception showed that sub variable reparation performed very well, while two others only performed well. Based on regression analysis, a model that explained relationship between after-sales service and WOM was meaningful. In other words, after sales services performed by Daya Motor encouraged consumers to do WOM. Key words: After Sales Service, WOM, Consumer.